Land Use Changes in Europe Processes of Change, Environmental Transformations and Future Patterns - Brouwer, F.M.; Thomas, A.J.; Chadwick, M.J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1991)
The patterns of land use that have evolved in Europe reflect the boundaries set by the natural environment and socio-economic responses to the needs of the population. Over the centuries man has been able to overcome increasingly the constraints placed on land use by the natural environment through the development of new technologies and innovations, driven by an increasing population and rising material expectations. However, activities are still ultimately constrained by natural limitations such as climatic characteristics and associated edaphic and vegetational features. A major problem for land management, in its broadest sense, can be a reluctance to foresee the consequent ecological changes. This means that mitigating strategies will not be implemented in time to prevent environmental degradation and social hardship, although in many parts of Europe, over some centuries, demands have been met in a sustainable way, by sound, prudent and temperate expectations that have dictated management regimes. The management of land in Europe has always been a complex challenge: land is the primary, though finite resource. DeciSions regarding the use of land and manipulation of ecosystem dynamics today may affect the long-term primary productivity of the resource. Decisions to change land use may be virtually irreversible; urbanization is an illustration of the influence of population density on the land resource.
1. Land Resources, Land Use and Projected Land Availability for Alternative Uses in the EC -- 2. Trends in the Transformation of European Agriculture -- 3. Future Land Use Patterns in Europe -- 4. The Role and Impact of Biophysical Determinants on Present and Future Land Use Patterns in Europe -- 5. Atmospheric Methane: Estimates of Its Past. Present and Future and Its Role in Effecting Changes in Atmospheric Chemistry -- 6. Perspectives on a Changing Hydroclimate: Land Use Implications -- 7. Dynamics in Land Use Patterns: Socio-economic and Environmental Aspects of the Second Agricultural Land Use Revolution -- 8. Climatic Change and Land Use Impact in Europe -- 9. Climatic Changes and Land Use Potential in Europe -- 10. Environmental Constraints on Agricultural Production -- 11. Potential Effects of Climate and Land Use Changes on the Water Balance Structure in Poland -- 12. Soil Erosion, Soil Degradation and Climatic Change -- 13. Salinization Potential of European Soils -- 14. Changes in Rates of Weathering and Erosion Induced by Acid Emissions and Agriculture in Central Europe -- 15. Potential for Acidification of Forest Soils in Europe -- 16. Historical Land Use Changes and Soil Degradation on the Russian Plain -- 17. Historical Land Use Changes: The Netherlands -- 18. Historical Land Use Changes: Sweden -- 19. Historical Land Use Changes: Poland -- 20. Historical Land Use Changes: Mediterranean Regions of Europe -- 21. Land Use Statistics in Natural Resource Accounting Systems -- 22. Analysis of Land Use Determinants in Support of Sustainable Development.
Keywords: Environmental management; Ecotoxicology; Nature conservation; Environmental Management; Ecotoxicology; Nature Conservation